Eksplorasi Simbolisme Tarian Torompio dalam Tradisi Suku Pamona - Patonga, Hermin Krisvila; Hatta, Ikhtiar; Resmiwati, Resmiwati; Badollahi, Muh. Zainuddin (CV. Social Politic Genius (SIGn), 2023)
This research aims to understand the symbolism and meanings of the Torompio dance among the Pamona indigenous people in Lambarese Village. This research uses an ethnographic analysis. Ethnographic analysis is an approach that begins with field facts, analyzes them based on cultural theories and relevant arguments to explore the cultural situation of the community, and ultimately yields a conclusion. The results show that the Torompio dance is a rich manifestation of symbolism and profound meaning, depicting complex interactions between humans, nature, and spirituality. The name “torompio” and the “paporapa” concept demonstrate how the Pamona indigenous people communicate values and emotions symbolically. Dance movement symbols reflect social and spiritual values and harmonious relations with nature. The transition of traditional attire from “karaba” to fabric and beads shows cultural adaptation in preserving traditions amidst changing times. The verses (kayori) underscore the symbiotic relationship between the community and nature and reflect a spiritual view of creation. All elements in the Torompio dance synergistically express the “Fervor of Love,” which is central to the cultural expression of the Pamona indigenous people. Therefore, it is recommended that the Department of Education and Culture of East Luwu Regency, the Lemba Pamona Luwu Indigenous Institution, and the Pamona indigenous people take strategic steps in preserving and promoting the Torompio dance. First, integrating the Torompio dance into the school education curriculum in East Luwu. Second, the Lemba Pamona Luwu Indigenous Institution should regularly organize workshops and cultural festivals featuring the Torompio dance as the main event. Third, the Pamona indigenous people are advised to continuously innovate and adapt their cultural expressions to modern times while maintaining the essence and original values of the Torompio dance. These initiatives will contribute to preserving the Torompio dance as an essential part of the cultural heritage and identity of the Pamona indigenous people while enriching Indonesia’s cultural diversity.